Literature Review : Penuaan Dini pada Kulit : Gejala , Faktor Penyebab dan Pencegahan - Rizkyah, Anna; Karimah, Salsabila Nurul (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2023)
Background: Premature aging is generally defined as the process of skin aging faster than its time, which is characterized by the appearance of facial wrinkles, dullness, and a different skin color when one enters one's 30s, resulting in the body losing its functions and abilities more quickly than normal. As many as 76% of womenin Indonesia are affected by premature aging. Objective: To review premature aging of the skin: Symptoms, causal factors, and prevention. Method: In this study we used a research method in the form of a literature review, namely a series of researchrelating to library data collection methods taken via Google Scholar with a vulnerable limit of 2010-2023. Results: Based on reviewed journals regarding premature aging of the skin, there is a relationship between a healthy lifestyle and premature aging. A healthy diet and lifestyle can prevent premature aging of the skin. Conclusion: The better a person's lifestyle and patterns, the more it prevents premature aging of the skin.